(3GdJUha Hjf GdZRGdi hGHf JjejI (B/s - (3GMeO, YHOGdaJGM eMeOs (Mansurah : Dar al-Wafa' lil Tiba'ah wa-al-Nashr wa al-Tawzi', 2000)
Sufism ; Ghazzali, 1058-1111; Ahmad ibn'Abd al-Halim Ibn Taymiyah , 1285 or 4 ; Islamic philosophy ; comparative study
Keywords: al-Ghazzali, -- 1058-1111 -- Views on Sufism; Ibn Taymiyah, Ahmad ibn'Abd al-Halim, -- 1263-1328 -- Views on Sufism; Sufism